MicroRNA-Mediated Control of Inflammation and Tolerance in Pregnancy - Kamity, Ranjith; Sharma, Surendra; Hanna, Nazeeh (Frontiers in Immunology, 2019)
Gestational age-dependent immune intolerance at the maternal-fetal interface might be a contributing factor to placental pathology and adverse pregnancy outcomes. Although the intrauterine setting is highly choreographed and considered to be a protective environment for the fetus, unscheduled inflammation might overwhelm the intrauterine milieu to cause a cascade of events leading to adverse pregnancy outcomes. The old paradigm of a sterile intrauterine microenvironment has been challenged, and altered microflora has been detected in gestational tissues and amniotic fluid in the absence of induction of significant inflammation. Is there a role for endotoxin tolerance at the maternal-fetal interface? Endotoxin tolerance is a phenomenon in which tissues or cells exposed to the bacterial product, particularly lipopolysaccharide, become less responsive to subsequent exposures accompanied by decreased expression of pro-inflammatory mediators. This could also be related to trained or experienced immunity that leads to the successful outcome of subsequent pregnancies. Adaptation to endotoxin tolerance or trained immunity might be critical in preventing rejection of the fetus by the maternal immune system and protecting the fetus from excessive maternal inflammatory responses to infectious agents; however, to date, the exact mechanisms contributing to the establishment and maintenance of tolerance at the maternal-fetal interface remain incompletely understood. There is now extensive evidence suggesting that microRNAs (miRNAs) play important roles in the maintenance of healthy pregnancy. miRNAs not only circulate freely in extracellular fluids but are also packaged within extracellular vesicles (EVs) produced by various cells and tissues. The placenta is a known, abundant, and transient source of EVs; therefore, our proposed model suggests that repeated exposure to infectious agents induces a tolerant phenotype at the maternal-fetal interface mediated by specific miRNAs mostly contained within placental EVs. We hypothesize that impaired endotoxin tolerance or failed trained immunity at the maternal-fetal interface will result in a pathological inflammatory response contributing to early or late pregnancy maladies.